The Incidence of Anemia and the Student Achievement Index at Midwifery Department, Poltekkes Kemenkes Aceh - Nurlaili Ramli; Lia Lajuna (Health Notions, 2019)
Anemia is a nutritional problem that is relatively difficult to overcome. The purpose of this study was to analyze the relationship between the events of Anemia and students achievement index in the Banda Aceh Midwifery program. The research design was a cross-sectional study, involving 163 participants, selected using simple random sampling. To get the data needed, this quantitative study used questionnaires, in-depth interviews and a hemoglobin device Quick-Check Set (Easy Touch) Testing System. Data were analyzed using Chi-square test. The results showed that there was a relationship between the incidence of anemia and the achievement index (p-value = 0.006). The incidence of anemia directly affects the students learning achievement indicating with the decreased immune system so it is susceptible to disease, decreases physical ability, learning activities thereby reducing their learning performance. Keywords: anemia; student achievement index; midwifery students